Learning Outcomes of Listening Comprehension Skills through Audio Visual and Interactive-Audio - Istifadah Istifadah; Taufiq Satria Mukti; Kartika Satya Noviafitri (Journal of English Language Teaching and Learning (JETLE), 2022)
This study aims to examine strategies and media bases in learning English-Listening Comprehension skills. The two strategies that are the subject of discussion are the Audio-Visual Media-based Strategy and the Interactive-Audio Strategy. Quantitative research was carried out by surveying the object of research and strengthened by interviews with several respondents at random to ensure that all respondents had received learning with two strategies. The object of this research is the students of the English Education Department at the State Islamic University of Maulana Malik Ibrahim Malang. All respondents in this survey are 34 respondents. Data analysis was carried out in a qualitative descriptive manner to interpret the percentage of the implementation of learning in the two strategies. The results showed that the Audio-Visual Strategy had a percentage point interval of 76.92%, which indicated that this strategy was in the "Good" category. While the Interactive-Audio Strategy has a percentage point interval of 50.48%, which indicates that this strategy is in the “Enough” category. From these results, it can be concluded that the Audio-Visual strategy provides maximum results when applied in Listening Comprehension Skill learning so that the Audio-Visual strategy is more effective